Bez Ludwika i panny służącej. Projekty nowoczesnych kuchni jako zwierciadło przemian roli kobiet w poodwilżowej Polsce - Szydłowska, Agata (Artium Quaestiones, 2021)
The development of a post-Stalinist modern kitchen in Poland was informed by the activities of different individual and institutional actors: experts in ‘professional’ home engineering, architects and designers and modernist taste-makers. The image of the model kitchen is surprisingly coherent: a rational laboratory kitchen, where the housewife’s work is orchestrated according to Taylorism-inspired rules that aim at reducing the burden of domestic chores and introducing modern and hygienic equipmentand attitudes. The discourse, inspired by similar discussions in Europe and United States, mainly by the works of Swedish Research Institute, reflects the prewar ideas of kitchen-laboratories and ‘home engineering’. What’s new and different is the temporal (limited to a short post-Thaw period) enthusiasm for open-plan kitchens presented as spaces where a housewife can seamlessly perform two duties at the same time: housework and care work. This phenomenon mirrors changing attitudes towards women’s roles in society which, in the post-Stalinist period, were marked by ongoing conservatism. Drawing on the concept of a ‘mediation junction’ and the historical production-consumption-mediation paradigm in design, the article traces changing attitudes towards women’s roles in society, reflected both in popular and professional discourses on kitchen design.